Intergrasi Sistem Minimum IoT Yang Handal Untuk Pertanian Berbasiskan Mikrokontroler dan Protokol Komunikasi - Arsanto Narendro; Yani Prabowo; Jan Everhard; Suwasti Broto; Tatang Wirawan Wisjhnuadji (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Traditional agriculture refers to farming that utilizes natural and local techniques, relying little on modern technology or chemicals. However, traditional agricultural systems face many challenges, including low productivity; traditional farming may not be as productive as modern methods. Additionally, dependence on weather conditions poses a significant barrier to production. To improve the quality and productivity of traditional agriculture, methodologies such as developing smart farming systems can be implemented. Smart farming applies technology in agriculture to enhance efficiency, productivity, and sustainability through sensors and IoT devices to manage and monitor agricultural activities more effectively. The smart farming system to be developed is based on the SCADA concept, where control of devices such as temperature sensors, soil moisture, light, and rainfall sensors, as well as actuators, is managed via the ModBus protocol based on the RS-485 RTU module. For controllers connected to the internet server, the ESP32 module will be used. Users can access the system using smartphones or laptops equipped with a wireless modem to establish remote connections via the internet. Thus, the application of this technology can significantly increase agricultural productivity and improve the efficiency of managing fields and crops. Users do not need to be physically present on-site, as the system can be controlled and monitored remotely from a distance.